The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s12028-021-01223-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of Near-Infrared Spectroscopy for the Detection of Delayed Cerebral Ischemia in Poor-Grade Subarachnoid Hemorrhage

Abstract: Background The objective of this study was to investigate the clinical feasibility of near-infrared spectroscopy (NIRS) for the detection of delayed cerebral ischemia (DCI) in patients with poor-grade subarachnoid hemorrhage (SAH) treated with coil embolization. Methods Cerebral regional oxygen saturation (rSO 2 ) was continuously monitored via two-channel NIRS for 14 days following SAH. The rSO 2 levels according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…In general, continuous lumbar drainage was maintained until 7 days after the treatment. Nimodipine (Samjin Pharmaceutical, Seoul, South Korea) was administered intravenously at a dose of 20 μg/kg/h to prevent cerebral vasospasm ( Park et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, continuous lumbar drainage was maintained until 7 days after the treatment. Nimodipine (Samjin Pharmaceutical, Seoul, South Korea) was administered intravenously at a dose of 20 μg/kg/h to prevent cerebral vasospasm ( Park et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The H-H grade was divided into two groups: lower H-H (I, II, and III) and higher H-H group (IV and V), and likewise Fisher grade was divided into a low grade (Fisher grades I and II) and high grade (Fisher grades III and IV) ( Kim et al, 2018 ). Severe cerebral vasospasm was defined as a decrease in vessel diameter of over 70% compared with baseline computed tomography angiography or magnetic resonance angiography ( Park et al, 2021 ). This study was approved by the Institutional Review Boards (IRB No: 2016-31, 2018-6, and 2019-06).…”
Section: Methodsmentioning
confidence: 99%
“…Although mainly used as an intraoperative monitoring tool in cardiac surgery, near-infrared spectroscopy (NIRS) has gained increasing awareness as a non-invasive modality option within the intensive care unit ( 50 , 51 ). The modality can display regional cerebral oxygen saturation (rSO2) in the frontal lobes and has previously been validated in stroke patients to correlate with cerebral blood flow through perfusion imaging ( 52 ).…”
Section: Modalitiesmentioning
confidence: 99%
“…More interestingly, the same 12% cut-off yielded a sensitivity of 94% (95% CI: 73–99%) and a specificity of 71% (95% CI: 53–85%) to detect DCI ( 59 ). Another study on 24 patients presenting with poor grade aSAH reported a sensitivity of 86% (95% CI: 67–98%) and specificity of 86% (95% CI: 67–96%) for DCI detection using a greater than 15% decrease in c-rSO 2 ( 60 ).…”
Section: Clinical Data—vasospasm DCI Prognosismentioning
confidence: 99%